Amplitude Analysis of the Decay B 0 → K0 Sπ+π − and First Observation of the CP Asymmetry in B 0 → K*(892)-π+; Physical Review Letters; Vol. 120, iss. 26 - Aaij R. Roel; Adeva B. Bernardo; Adinolfi M. Marco; Vagner A. R. Aleksandr Rudolfovich (2018, 2018)
Title screen